2018
DOI: 10.1111/josi.12280
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the Masculinity Contest Culture Scale

Abstract: We developed and validated a 20‐item Masculinity Contest Culture (MCC) scale as a workplace culture assessment. Participants indicated agreement or disagreement with workplace norm statements beginning with a common stem (“In my work environment…”). Exploratory (Study 1) and confirmatory (Study 2) factor analyses yielded four MCC subfactors: Show No Weakness, Strength and Stamina, Put Work First, and Dog Eat Dog. CFA and reliability analyses supported a second‐order factor (with four subfactors), consistent wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
125
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(134 citation statements)
references
References 45 publications
7
125
0
2
Order By: Relevance
“…Considering that the toxic leadership measure and masculinity contest culture measure had high correlations, we also examined a four‐factor model with the indicators for toxic leadership and MCC all loaded onto one common factor. Consistent with Glick et al.’s () discriminant validity findings, our results supported that the toxic leadership and masculinity contest culture scales assess distinct constructs. Specifically, the four‐factor model fit the data significantly worse than the five‐factor model, χ 2 (623, N = 1,000) = 4366.64, p < .01; CFI = .88, TLI = .88, RMSEA = .08, SRMR = .07; ∆χ 2 (∆ df = 4) = 2346.85, p < .01.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Considering that the toxic leadership measure and masculinity contest culture measure had high correlations, we also examined a four‐factor model with the indicators for toxic leadership and MCC all loaded onto one common factor. Consistent with Glick et al.’s () discriminant validity findings, our results supported that the toxic leadership and masculinity contest culture scales assess distinct constructs. Specifically, the four‐factor model fit the data significantly worse than the five‐factor model, χ 2 (623, N = 1,000) = 4366.64, p < .01; CFI = .88, TLI = .88, RMSEA = .08, SRMR = .07; ∆χ 2 (∆ df = 4) = 2346.85, p < .01.…”
Section: Resultssupporting
confidence: 91%
“…As one of the first empirical studies to confirm the basic tenets of the masculinity contest culture construct, our findings are noteworthy and generally consistent with related studies reported in this special issue documenting the mostly negative outcomes associated with masculinity contest cultures (Glick et al., ; Rawski & Workman‐Stark, ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations